Knowledge translation in athletic training: considerations for bridging the knowledge-to-practice gap - Bacon, C. E. W.; Lacy, A. M. P.; Lam, K. C. (Journal of Athletic Training, 2021)
As the athletic training profession continues to embrace evidence-based practice, athletic trainers should not only critically appraise the best available evidence but also effectively translate it into clinical practice to optimize patient outcomes. Whereas previous authors investigated the effectiveness of educational interventions on increasing knowledge of critical appraisal of evidence, little attention has been given to strategies for both researchers and clinicians to effectively translate evidence into clinical practice. The use of knowledge translation strategies has the potential to bridge the knowledge-to-practice gap, which could lead to reduced health costs, improved patient outcomes, and enhanced quality of care. The purpose of this article is to (1) highlight the current challenges preventing the successful translation of evidence into practice, (2) discuss knowledge translation and describe the conceptual frameworks behind the effective translation of evidence into practice, and (3) identify considerations for athletic trainers as they continue to provide high-quality patient care in an evidence-based manner.